2017
DOI: 10.1016/j.avsg.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gender Differences on Short-term Outcomes in Patients with Type B Aortic Dissection

Abstract: Introduction Gender-related differences in type B aortic dissection (TBAD) presentation and outcomes are not well understood. The objective of this study is to assess the impact of gender on short-term outcomes in patients with TBAD. Methods Patients with TBAD were identified from National Inpatient Sample datasets from 2009–2012 according to previously published methods. The primary outcomes of interest were in-hospital mortality and major complications (renal, cardiac, pulmonary, paraplegia, and stroke-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 18 publications
2
34
1
Order By: Relevance
“…Females tended to be older and generally more chronically ill, with higher rates of diabetes. 13 Though there is no significant statistics difference of age in different genders, females were older and more likely to present with atypical pain than males in our study. Differences in inhabit, phenotype, diet, and customs between Western and Chinese populations might also affect treatment outcomes.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Females tended to be older and generally more chronically ill, with higher rates of diabetes. 13 Though there is no significant statistics difference of age in different genders, females were older and more likely to present with atypical pain than males in our study. Differences in inhabit, phenotype, diet, and customs between Western and Chinese populations might also affect treatment outcomes.…”
Section: Discussioncontrasting
confidence: 55%
“… 12 An observational study of 9855 type B AAD patients indicated that compared with men, women were more likely to experience endovascular and sustain a perioperative cardiac event with open surgery. 13 In Chinese with AAD, gender is also not independently related to long‑term clinical outcomes. 14 Our study may have a better assessment of gender-related short-term outcomes disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data indicate that women are more likely to undergo thoracic endovascular aortic repair than open repair, and have a higher mortality and lower long- term survival after surgery. 71,72…”
Section: Thoracic Aortic Aneurysms and Acute Aortic Dissections (Tmentioning
confidence: 99%
“…There was little difference in early outcomes in the matched groups; pulmonary complications were more common in women, and persistent paraplegia was slightly more common in men. By using National Inpatient Sample data on 9855 open and endovascular repairs of acute distal aortic dissection, Liang and colleagues 34 found higher rates of postoperative paraplegia in men than in women after propensity weighting.…”
Section: Deathmentioning
confidence: 99%